A case of successfully resected metachronous gastric and gallbladder metastases from pancreatic body cancer - Makoto Takahashi; Hideyuki Yoshitomi; Atsushi Kato; Katsunori Furukawa; Tsukasa Takayashiki; Satoshi Kuboki; Shigetsugu Takano; Kensuke Sugiura; Keishi Kawasaki; Masaru Miyazaki; Masayuki Ohtsuka (Surgical Case Reports, 2019)
Abstract Background Pancreatic ductal adenocarcinoma (PDAC) readily metastasizes to the lymph nodes, liver, lung, and peritoneum; however, gastric and gallbladder metastases are rare. We report a case of metachronous gastric and gallbladder metastases from PDAC. Case presentation The patient is a 71-year-old man who underwent distal pancreatectomy for PDAC. Seventeen months after the surgery, a 30-mm nodule was detected at the lesser curvature of the stomach, which was diagnosed as recurrence of PDAC in the lymph nodes. He then received gemcitabine and S-1 combination chemotherapy for 6 months. Because tumor size remained approximately the same and tumor marker levels decreased, total gastrectomy and cholecystectomy were performed. Pathological examination showed well-differentiated tubular adenocarcinoma in the subserosa and muscularis propria of the stomach and gallbladder. The patient remains alive at 41 months after the second surgery with liver metastasis. Conclusion We reported a rare case of metachronous gastric and gallbladder metastases from pancreatic body cancer.